Modes of investment of Social Islami Bank Limited : a study on Dewanhat Branch, Chittagong - Begum, Jhahanara (BRAC University, 2017)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Masters of Business Administration, 2017